Examining barriers, physical activity, and weight change among parents and nonparents in a weight loss intervention - Brooke T. Nezami; John M. Jakicic; Wei Lang; Kelliann Davis; Deborah F. Tate (Wiley, 2020)
Summary Introduction Little is known about the influence of children in the home on physical activity and weight among adults in weight loss interventions. This study evaluated the association between number of children in the home, weight loss, and weight regain in a behavioural weight loss intervention, and whether those relationships were mediated in sequence by physical activity barriers and physical activity changes. Methods The sample included 267 participants from a randomized trial who had complete data on study variables. Variables at baseline, 6, and 18 months included physical activity barriers, objectively measured minutes of moderate‐to‐vigorous physical activity (MVPA), and objectively measured weight used to calculate percent weight loss (PWL) from baseline to 6 months and percent weight regained (PWG) from 6 to 18 months. Results A greater number of children in the home was associated with less PWL at 6 months. This relationship was mediated by greater baseline physical activity barriers and a smaller increase in MVPA at 6 months. The mediated effect was no longer significant when controlling for changes in dietary intake. There was no relationship between number of children and PWG from 6 to 18 months. Conclusions Parents may need unique intervention supports to overcome barriers to initiation of physical activity to help them reach optimal weight loss.